EASTERN AUSTRALIA: A POSSIBLE SOURCE OF DUST IN EAST ANTARCTICA INTERGLACIAL ICE - Revel-Rolland M.; Deckker P.De.; Magee J.W.; Delmonte B.; Hesse P.P.; Basile-Doelsch I.; Grousset F.; Bosch D. (My University, 2006)
The Australian continent is characterised by an extremely variable surficial geochemistry, reflecting the varied lithology of Australian basement rocks. Samples representative of Australian aeolian dust have been collected in (1) regions where meteorological records, satellite observation and wind erosion modelling systems have indicated frequent dust activity today (mainly the Lake Eyre Basin), and (2) from deposits of mixed dust materials. The 87Sr/86Sr and 143Nd/144Nd isotopic composition of the fine (< 5 μm) fraction of Australian dust samples was measured for comparison with the Sr and Nd isotopic composition of fine aeolian dust that reached the interior of the East Antarctic Plateau. The isotopic field for Australian dust is characterised by 87Sr/86Sr ratios ranging from 0.709 to 0.732 and εNd(0) between - 3 and - 15. The low Sr radiogenic values and εNd(0) of - 3 obtained for Lake Eyre samples are explained by the lithology of the Lake Eyre catchment showing a dominance of Tertiary intraplate volcanic material. These new data show that the dust contribution from Australia could have been dominant during interglacial periods (Holocene and Marine Isotopic Stage 5.5) to Antarctica. During glacial times, studies have shown that the South American dust isotopic signature overlaps the glacial Antarctic dust field suggesting this region as dominant aeolian dust source. However, the Australian Lake Eyre dust isotopic signature partially overlaps with the Antarctic glacial dust signature. We propose that the relatively greater contribution of Australian dust inferred for Antarctic interglacial ice compared with glacial ice is not directly reflective of changes in dust transport pathway, but instead is related to a differential weakening of the South American sources during interglacial time with respect to the Australia sources. Our findings have implications for interglacial versus glacial atmospheric circulation, at least in the Southern Hemisphere. © 2006 Elsevier B.V. All rights reserved.
Keywords: AUSTRALIAN AEOLIAN DUST; EAST ANTARCTICA ICE CORE DUST; LAKE EYRE BASIN; SR AND ND ISOTOPES; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен